2017
DOI: 10.1186/s41016-016-0070-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of patients with pituitary stalk thickening: a review of 159 cases from one medical center

Abstract: Background: Pituitary stalk thickening (PST) used as an imaging diagnosis plays a major role in diagnosis and treatment of the hypothalamus and pituitary disease at an early stage. Up until now, several lines of systematic investigations have been conducted among adolescents, and the results indicated that PST is possibly one of the principal early manifestations of sellar region tumor. To characterize the major clinical features of PST and to identify the most effective treatments we conducted this study. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Numerous studies confirmed that CDI was the most common initial symptom of PST ( 2 , 4 , 9 ). Every pediatric patient with CDI should undergo MRI imaging of the pituitary hypothalamic axis to confirm the diagnosis and perhaps determine the etiology ( 10 ).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Numerous studies confirmed that CDI was the most common initial symptom of PST ( 2 , 4 , 9 ). Every pediatric patient with CDI should undergo MRI imaging of the pituitary hypothalamic axis to confirm the diagnosis and perhaps determine the etiology ( 10 ).…”
Section: Discussionmentioning
confidence: 95%
“…There are various reasons for PST, such as neoplastic, inflammatory or infectious diseases ( 1 ). PST mainly affects teenagers and is often detected with magnetic resonance imaging (MRI) in patients with central diabetes insipidus (CDI) ( 2 ). Pituitary stalk lesions are sometimes accidentally detected during brain MRI.…”
Section: Introductionmentioning
confidence: 99%
“…In the Mayo Clinic study, 43 out of 152 enrolled patients presented with DI, with at least 1 of the anterior pituitary axes being insufficient in 49 cases (32%), and with hypogonadotropic hypogonadism as the most common deficit [ 13 ]. Cai et al confirmed anterior pituitary lobe dysfunction in almost half of the patients [ 15 ]. Furthermore, a high percentage of GHD (84.9%) and central hypogonadism (64.1%), followed by secondary hypothyroidism and hypocorticism (both at 45.2%) were described by Doknic et al [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…1, 2 ). PST mainly affects teenagers and is often detected with magnetic resonance imaging (MRI) in patients with central diabetes insipidus (CDI) [ 1 ]. Sometimes, pituitary stalk lesions are accidentally detected during brain MRI.…”
Section: Introductionmentioning
confidence: 99%